The American Woman, 2003-2004
XVII, 399 p.
Keywords: The American Woman is an established, widely respected series on the status of American women, prepared biannually by the Women's Research and Education Institute (WREI). The purpose of the series is to provide an important, convenient, and timely source of accessible and 'user-friendly' information on American women to the media, students and scholars, advocates for women's equity, and policymakers. Each edition of the series focuses on a particular theme, and the ninth edition will address young women between the ages of 25 and 35. Contributors - all experts in the field of women's issues - will explore the opportunities and challenges confronting the young women who are the daughters of the baby boomer generation. A focus on young women will bring into sharp relief how much has changed in the decades since 1960 and how much remains the same. A statistical portrait will accompany the volume, including user-friendly charts and graphs that provide readers with the hard numbers that underlie the trends shaping women's experiences.